Detection of primary clarithromycin resistance of Helicobacter pylori and association between cagA (+) status and clinical outcome - Yula, Erkan; Nagiyev, Toğrul; Kaya, Ozlem Aycan; Inci, Melek; Celik, M Murat; Köksal, Fatih (Folia microbiologica, 2013)
Helicobacter pylori was examined in 110 patients (82 (74.5) with gastritis, 18 (16.4) with duodenitis, six (5.5) with duodenal ulcer and gastroesophageal reflux, and four (3.6 %) with normal) with gastrointestinal problems living in rural area, no history of macrolide use, and detected by culture (71.8) or direct detection from gastric biopsies by PCR (82.7 %). Also, cagA gene was identified using PCR and was found positive in 68/91 (74.7 %) strains. The prevalence of clarithromycin-resistant H. pylori was investigated by two methods including PCR-RFLP (7.7 (A2142G 1.1 and A2143G 6.6 %)) and twofold agar dilution (8.9 %) to detect phenotypic and genotypic status simultaneously. Among all the H. pylori positive patients, eight (8.8 %) isolates were found to be resistant to clarithromycin by at least one of the AD and/or PCR-RFLP methods. H. pylori positive rates were significantly correlated with patients' sex, age, and endoscopic findings (p = 0.040, <0.001 and <0.001, respectively). There were no differences in gender or endoscopic findings related to cagA (+) and cagA (-) patients. The gene of cagA was not significantly helpful in predicting the clinical outcome of H. pylori infection alone. In conclusion, we revealed that there was a low prevalence of primer clarithromycin resistance in patients living in rural area with no history of macrolide use. The prevalence of mutant strains among the macrolide-resistant H. pylori varies even geographically between close provinces.
Keywords: výsledek terapie; Young Adult; žaludeční sliznice; polymerázová řetězová reakce; Male; Rural Population; Turkey; Bacterial Proteins; Virulence Factors; mladý dospělý; Drug Resistance, Bacterial; antibakteriální látky; Microbial Sensitivity Tests; Adult; biopsie; venkovské obyvatelstvo; dospělí; mužské pohlaví; klarithromycin; antigeny bakteriální; faktory virulence; Helicobacter Infections; Turecko; Treatment Outcome; DNA, Bacterial; DNA bakterií; lidé; ženské pohlaví; Anti-Bacterial Agents; Clarithromycin; bakteriální léková rezistence; Humans; mikrobiální testy citlivosti; bakteriální proteiny; Helicobacter pylori; polymorfismus délky restrikčních fragmentů; Antigens, Bacterial; Biopsy; Polymerase Chain Reaction; Female; lidé středního věku; Gastric Mucosa; infekce vyvolané Helicobacter pylori; Polymorphism, Restriction Fragment Length; Middle Aged